(untitled) (Tanzania Medical Journal, 2010)
Background: Minor oral surgical procedure is any intervention that does not penetrate a body cavity. The procedure does not involve general anaesthesia or respiratory assistance. Objectives: The aim of this study was to document types of minor oral surgical procedures performed on patients attending Muhimbili National Hospital (MNH) for a period of 5 years. Study design: This was a retrospective study based on the hospitaldata retrieved from February 2003 to February 2007. Study population: Patients who had undergone minor oral surgical procedures at the Department of oral surgery and oral pathology. Methodology: A sample of 850 patients was obtained from the treatment files of the patients who had undergone minor oral surgical procedures during the period of review. Demographic data and different procedures were recorded, entered into the computer and analysed using SPSS programme version 11. Results: Among 850 patients, who had undergone minor oral surgical procedures, 509 were males and 341 were females. Males (59.9%) were more treated compared to females (40.1%) and the most age groups treated were 21-30 and 31-40 with each group comprising 36.6% and 23.2% of minor oral surgical procedures respectively. The age groups 61-70, 71-80 and 81-90 were the least treated. Disimpaction (28.8%) was the commonest procedure which was performed followed by incisional biopsy (22.2%) and IMF (16.3%) while FNAC and enucleation were the least performed procedures. Conclusion: Most of the minor oral surgical procedures performed on patients at our centre were disimpaction, incisional biopsy, IMF and cystectomy. FNAC was the least performed procedure. The factthat this study is a retrospective study it does not provide a true picture of minor oral surgical procedures performed at our centre. Therefore, there is a need to conduct a prospective study. Key words: Oral surgical procedure Muhimbili